1990
DOI: 10.1063/1.346383
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Cu gettering at a thermally grown SiO2/Si interface

Abstract: SiO2 film of 1500-Å thickness has been grown by a conventional thermal dry oxidation process on commercial Si(111) and Si(100) wafers. A secondary-ion mass spectrometry study of the SiO2/Si structure showed that a gettering of Cu atoms, which were present in the Si wafers as residual impurities, has occurred at the SiO2/Si interface due to the thermal dry oxidation process. The areal concentration of the Cu atoms at the interface has been found to depend on the Cu concentration in the Si wafers. Areal concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The oxide layer in our test structures was intentionally chosen thicker than that in typical production wafers in order to separate metal diffusion profiles and equilibrium metal concentration within the oxide from metals accumulated at Si/SiO 2 interfaces. Such accumulations were observed under certain conditions in copper-and iron-contaminated wafers in the past [14][15][16][17][18][19], and are also visible in our experimental data plotted in figure 4.…”
Section: Experimental: Diffusivity and Segregation Coefficient Of Fe ...supporting
confidence: 78%
“…The oxide layer in our test structures was intentionally chosen thicker than that in typical production wafers in order to separate metal diffusion profiles and equilibrium metal concentration within the oxide from metals accumulated at Si/SiO 2 interfaces. Such accumulations were observed under certain conditions in copper-and iron-contaminated wafers in the past [14][15][16][17][18][19], and are also visible in our experimental data plotted in figure 4.…”
Section: Experimental: Diffusivity and Segregation Coefficient Of Fe ...supporting
confidence: 78%
“…It was reported that due to oxidation, the intrinsic Cu gettering occurred at the thermally grown SiO 2 /Si interface. 19 Another possibility for Cu incorporation may arise from the problem of the instrument in this study. The VN barrier and subsequent Cu layer were sputter-deposited in the same chamber, as already described, resulting in the occurrence of an extremely small amount of pre-existing Cu at the surface of SiO 2 .…”
Section: Application Of a Thin Vn Barrier In Cu/ Siomentioning
confidence: 99%
“…Bai et al demonstrated that copper is gettered to the Si/SiO 2 interface during thermal growth of a silicon oxide layer. 20 Strained Si would also be a possible getter site but only if the silicon lattice is under tensile strain. 16 The molecular volume of the oxide precipitate is larger than the molecular volume of Si.…”
mentioning
confidence: 99%